Environmental Performance and Firm Value: Evidence from Sharia-Compliant Manufacturing Firms in Indonesia (2020-2024) - Ahmad Zuliansyah; Khusnul Qotimah; Nur Wahyu Ningsih (Goodwood Publishing, 2026)
Purpose: This study investigates whether environmental performance affects firm value among Sharia-compliant manufacturing firms in Indonesia during 2020–2024. Research Methodology: A quantitative causal-associative approach was used. The sample included six firms from the Indonesia Sharia Stock Index (ISSI), yielding 30 firm-year observations through purposive sampling. Environmental performance was measured using PROPER ratings, and firm value was measured using the Price-to-Book Value (PBV). Simple linear regression was conducted in SPSS 25 after classical assumption tests Results: Environmental performance showed a positive but statistically insignificant relationship with PBV (p > 0.05), suggesting that it is not yet a decisive factor in market valuation. Conclusions: This study concludes that Environmental Performance does not have a statistically significant effect on Firm Value among manufacturing companies listed in the Indonesia Sharia Stock Index (ISSI) during the 2020–2024 period. Although the relationship is positive, the effect is not strong enough to significantly influence firm value. These findings indicate that environmental performance, as measured in this study, has not yet become a primary consideration in market valuation of Sharia-compliant manufacturing firms. This suggests that other financial or governance factors may play a more dominant role in determining firm value. Limitations: The study uses a small sample, a single environmental proxy (PROPER), and a bivariate model that may not capture other key determinants of firm value. Contributions: The findings enrich environmental accounting evidence in the context of Islamic equity and provide practical insights for firms, investors, and regulators to strengthen credible environmental practices and disclosures.